An Initial Study of the Water Pollution Analysis at Residential, Office Building and Industrial Area’s in Bogor - Izzati, Titia (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
The purpose of this study is to find out the level of acidity (pH) and electrical conductivity (EC) in the ground water in Residential, Office Building and Industrial Area in Bogor. This study used pH meter to determine the level of acidity and EC meter to find out the electrical conductivity. The method in this research was to collect ground water samples randomly in several places in Bogor area. The result of this research showed that the ground water in Bogor area was categorized as normal, because the pH was in range of 7.23 to 7.51